Assessing and forecasting the long-term impact of the global financial crisis on manufacturing sales in South Africa - Tendai Makoni; Delson Chikobvu (Economies, 2023)
Sales forecasting is a crucial aspect of any successful manufacturing organisation as it provides the foundation for investment, employment development, and innovation. The Global Financial Crisis (GFC) had a negative impact on the manufacturing sector in South Africa (SA) and the rest of the world. The objective of this paper is to analyse the trend of manufacturing sales before, during, and after the GFC and to quantify the impact of the GFC on the total manufacturing sales in SA. The time-series-based Box-Jenkins methodology is used to achieve the objective. The study used Statistic South Africa's data on monthly total manufacturing sales in SA from January 1998 to December 2022. Total manufacturing sales exhibit strong seasonality. The ACF, PACF, and EACF plots, as well as the AIC, BIC, RMSE, and MAE, suggest the SARIMA(2,1,2)(2,1,1)12 model as the best model for explaining and forecasting manufacturing sales in SA. The SA manufacturing sector was negatively impacted by the GFC, as evidenced by the comparison between actual data and projections based on a historical path prior to the GFC. Manufacturing sales are recovering from the GFC but have not reached potential levels that could have been achieved without the crisis. The SA manufacturing sector may take time to reach the expected/projected sale levels that could have been achieved in the absence of the GFC.
Keywords: 330; South Africa; manufacturing sales; forecasting; global financial crisis